GROWING Nutritious Foods, GROWING Futures. Addressing Gender Inequities to Enable the Nutritional and Financial Security of Women in Northern Ghana - Temesgen, B.B.; Loriba, A. (International Potato Center, 2024)
Building healthier and more sustainable food systems while reducing poverty is a major goal of the Ghanaian government. The GROWING project recognizes that tackling gender inequities in Northern Ghana is the key for an integrated climate-smart agriculture-nutrition-marketing approach to truly make a difference to the nutritional and financial security of women and the households they reside in. Over 4.5 years, an innovative approach facilitating GROWING Futures Clubs to exploit the potential of selected nutritious foods will be implemented and valuated.